(untitled) (Asian Journal of Agriculture, 2021)
Abstract. Awadhpersad VRR, Ori L, Ansari A. 2021. Production and effect of vermiwash singly and in combination with vermicompost on the growth, development, and productivity of tomatoes in the greenhouse in Suriname. Asian J Agric 5: 29-34. In Suriname farmers often largely rely on high inputs of synthetic fertilizers and pesticides to achieve high yield. To overcome this, sustainable agriculture seeks to introduce agricultural practices that are environmentally sound, economically viable, and socially supportive. In the present study, the effect of vermicompost and vermiwash and in combination was evaluated on the growth and yield of tomato (Lycopersicon esculentum Mill.) in the greenhouse. The experiment was a Randomized Block Design with four treatments and three replications. The growth parameters were measured for plant height, shoot wet and dry weight, root weight, and length, and yield in terms of the number of fruits and fruit weight. The produced vermiwash was a brownish colored liquid and had all the essential macro and micro plant nutrients, which indicates an environmentally friendly enriched nutrient liquid fertilizer for sustainable agriculture. The research results at harvest time indicated that the plant height, shoot fresh and dry weight, root weight, root density, root length, yield and fruit weight were higher for the plants treated with a combination of vermicompost and vermiwash. It was also noted that the flowering and fruiting ratio were significantly enhanced by application of vermiwash as a foliar spray. The combination of vermicompost and vermiwash (50 g + 50 mL) significantly (p < 0.05) resulted in the highest yielding plants, followed by vermiwash (100 mL) and vermicompost (100 g).